Comparison of the efficacy and safety of remimazolam and propofol for fiberoptic bronchoscopy in older patients: a prospective, randomized controlled study - Binggao Chai; Jiaxi Guo; Zhiwei Xu; Tao Chen; Hongquan Wang; Zhenqiang Zhu; Jian Zhong; Kanzheng Chen; Jianlong Du; Xianhui Kang (BMC Geriatrics)
Abstract Objective The aim of this study was to compare the efficacy and safety of remimazolam with those of propofol in older patients undergoing fiberoptic bronchoscopy with preserved spontaneous breathing. Methods Sixty older patients were randomly and equally divided into a remimazolam group (group R) and a propofol group (group P). Both groups received 0.15 µg/kg of sufentanil for analgesia. Group R received an initial dose of 0.2 mg/kg remimazolam and was injected with a maintenance dose of 1 mg/kg/h. Group P received an initial dose of 2 mg/kg propofol and was injected with a maintenance dose of 4 mg/kg/h. The primary evaluation indicators were the success rate of sedation and the incidence of hypotension. The secondary evaluation indicators were respiratory depression, hypertension, tachycardia, bradycardia, awakening time, quality of recovery-15 (QOR-15) score, patient satisfaction, physician satisfaction, and adverse events. Results Success rates of sedation were similar between group R (96.7%) and group P (100%). The incidence of hypotension in group R was lower than that in group P (2/30 vs. 10/30, p = 0.01). Respiratory depression was lower in group R than in group P (3/30 vs. 10/30, p = 0.03). Fewer patients reported injection pain in group R (0/30 vs. 7/30, p = 0.01). There were no significant differences in hypertension, tachycardia, bradycardia, awakening time, QoR-15 score, patient satisfaction, physician satisfaction, or adverse events between the two groups. Conclusions Remimazolam has a high sedation success rate for painless fiberoptic bronchoscopy in older patients, and the incidence of hypotension and respiratory depression is lower than that of propofol. Remimazolam may be a better choice for sedation during painless fiberoptic bronchoscopy in older patients with preserved spontaneous breathing. Trial registration ChiCTR2300069041; 6/3/2023.